Pendidikan Toleransi Beragama Disekolah Menengah Kejuruan Negeri 1 Wonosobo - Arum Rizqi Aprilia; Ahmad Zuhdi; Salis Irvan Fuadi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the implementation of religious tolerance education at Wonosobo State Vocational High School 1 and to identify the supporting and inhibiting factors in the process of its internalization. This research employs a qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that religious tolerance education is not only applied in classroom learning but is also manifested in the social life of the school community. The school provides worship facilities for non-Muslim students, invites external religious teachers, and adjusts the activity schedule so as not to interfere with religious practices. Both Muslim and non-Muslim teachers actively foster mutual respect and inclusivity among students. The main supporting factors include open-minded school leadership, a school culture that appreciates diversity, and interfaith collaboration among teachers. Meanwhile, inhibiting factors involve social interactions among students that occasionally lead to friction, as well as limited monitoring of students' behavior outside school, particularly on social media. In general, the implementation of religious tolerance education at this school has been effective and can serve as a model for applying diversity values in education.